Rethinking the apocalypse: Zeno's Conscience and Death Stranding. - Bartoloni, Paolo; Bianchi, Enea (Journal for Cultural Research, 2024)
The moment we live in is a moment of multiple crisis – environmental, political, economic, and viral – a moment, that is, where the reality of damage, fallibility and faultiness, and the ensuing fear, anxiety, rage, trauma, protest, and mobilisation have reached a critical point. Past and present narratives of crisis and trauma can help navigate this process. In this article we have chosen to focus on Italo Svevo's Zeno's Conscience (1923) and Hideo Kojima's videogame Death Stranding (2019) for several reasons. The most important of all are Svevo's and Kojima's choices to deal with the trauma of crisis by emphasising and investigating the process leading to crisis, and of focusing on the zone in-between the 'normal' and the unknown. In so doing both narratives underscore the significance of ruins, desolation and the broken as a backdrop for rediscovering everyday life and forging meaningful connections in a fragmented world.